2001
DOI: 10.1210/jcem.86.2.7185
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovary Syndrome Is Associated with Obstructive Sleep Apnea and Daytime Sleepiness: Role of Insulin Resistance1

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder of premenopausal women, characterized by chronic hyperandrogenism, oligoanovulation, and insulin resistance. Obstructive sleep apnea (OSA) and excessive daytime sleepiness (EDS) are strongly associated with insulin resistance and hypercytokinemia, independently of obesity. We hypothesized that women with PCOS are at risk for OSA and EDS. Fifty-three women with PCOS (age range, 16-45 yr) and 452 control premenopausal women (age range, 20-42)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(53 citation statements)
references
References 21 publications
2
50
0
1
Order By: Relevance
“…Tasali and coworkers assessed sleep quality, risk of sleep apnea and daytime sleepiness using three questionnaires and found that among 40 women with PCOS, 75% were at high risk for sleep apnea on Berlin Questionnaire, 63% had poor sleep quality as assessed by the Pittsbugh Sleep Quality questionnaire and 45 % had chronic daytime sleepiness as defined by the Epworth Sleepiness Scale (22). Women with PCOS reported more daytime sleepiness (as defined by Epworth Sleepiness Scale) than did controls in two other studies (10, 11). In one of these studies, the relation between PCOS and daytime sleepiness was reported to remain significant even after controlling for BMI (11).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Tasali and coworkers assessed sleep quality, risk of sleep apnea and daytime sleepiness using three questionnaires and found that among 40 women with PCOS, 75% were at high risk for sleep apnea on Berlin Questionnaire, 63% had poor sleep quality as assessed by the Pittsbugh Sleep Quality questionnaire and 45 % had chronic daytime sleepiness as defined by the Epworth Sleepiness Scale (22). Women with PCOS reported more daytime sleepiness (as defined by Epworth Sleepiness Scale) than did controls in two other studies (10, 11). In one of these studies, the relation between PCOS and daytime sleepiness was reported to remain significant even after controlling for BMI (11).…”
Section: Discussionmentioning
confidence: 81%
“…Women with PCOS reported more daytime sleepiness (as defined by Epworth Sleepiness Scale) than did controls in two other studies (10, 11). In one of these studies, the relation between PCOS and daytime sleepiness was reported to remain significant even after controlling for BMI (11). In a more recent study, it was found that a significant number of reproductive-age women with PCOS were at high risk for OSA based on Berlin Questionnaire (23).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Vfogel et al (2000) found that 44% of women with PCOS had OSA compared with 0% in age-and BMI-matched control subjects. Vgontzas et al (2000) found that the odds ratio for having OSA in women with PCOS versus control subjects was 30.6.…”
Section: Primary Sleep Disorders In Epilepsymentioning
confidence: 98%
“…Women with PCOS also have increased risk for OSA compared with reproductively normal control women of comparable BMI [113, 114], and OSA may be a risk factor for glucose intolerance in affected women. Indeed, multiple studies have demonstrated that sleep restriction is an independent risk factor for insulin resistance and decompensation in glucose tolerance in the general population [115].…”
Section: Metabolic Phenotype In Pcosmentioning
confidence: 99%